Buddhism and the transformation of old age in medieval Japan - Drott, Edward Robertson (University of Hawaiʻi Press, 2016)
Gods of the earth and the making of the vital center -- "Lamenting gray hair" : the poetics of retirement in early Japan -- Decrepit demons and defiled deities : elders at the crossroads in late Heian Japan -- Between this world and the next : reappraising the aged body in medieval Japan -- From outcast to saint : overcoming pollution in an age of decline -- The eccentric avatar : reimagining the body of the bodhisattva in early medieval engi -- The graying of the gods : the return of the okina kami in medieval myth -- "Tranquil heart, gazing afar" : reimagining the aged body in noh